2018
DOI: 10.1097/md.0000000000009608
|View full text |Cite
|
Sign up to set email alerts
|

Isolated skeletal muscle recurrence of an originally nodal diffuse large B cell lymphoma

Abstract: Rationale:Diffuse large B cell lymphoma (DLBCL) is a malignancy of the B cells with extranodal primary involvement being estimated at 30% to 40% of cases. Primary skeletal muscle presentation of DLBCL is extremely rare, with an estimated incidence of about 0.5% of extranodal lymphomas, presenting mostly in the lower extremities. The possible mechanisms of muscle involvement of DLBCL include primary extranodal disease, extension from adjacent organs (such as lymph nodes) or disseminated disease.Patient concerns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…3,4 The most commonly affected muscles are the muscles of the extremities, [14][15][16] which has also been noted in the canine cases. Recurrence of multicentric nodal lymphoma within the muscle has also been reported in people, 17,18 as has been muscular and cutaneous lymphoma as a part of disseminated disease. 19 A case of primary skeletal muscle non-Hodgkin's B-cell lymphoma with cutaneous involvement and without evidence of other systemic dissemination has been reported in a male patient, although no immunophenotyping of the cutaneous lesions was undertaken.…”
Section: Discussionmentioning
confidence: 93%
“…3,4 The most commonly affected muscles are the muscles of the extremities, [14][15][16] which has also been noted in the canine cases. Recurrence of multicentric nodal lymphoma within the muscle has also been reported in people, 17,18 as has been muscular and cutaneous lymphoma as a part of disseminated disease. 19 A case of primary skeletal muscle non-Hodgkin's B-cell lymphoma with cutaneous involvement and without evidence of other systemic dissemination has been reported in a male patient, although no immunophenotyping of the cutaneous lesions was undertaken.…”
Section: Discussionmentioning
confidence: 93%
“…This feature may reflect the degree of muscle involvement [ 11 , 27 ] and correlate with histological findings that show neoplastic lymphocytes surrounding and invading myofibrils [ 27 , 28 ]. Color and power Doppler US may show hypervascularity [ 25 , 29 ]. Real-time US-guided core needle biopsy is often used for diagnosis of skeletal muscle lymphoma, and was applied in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of chemotherapy and immunotherapy (R-CHOP) with or without radiation therapy is considered standard therapy for DLBCL [ 32 ]. This approach achieves a good response in patients with skeletal muscle lymphoma [ 29 , 32 , 33 ]. However, a meta analysis [ 24 ] revealed that DLBCL of the soft tissue is aggressive and associated with poor prognosis, requiring further studies to better characterize this peculiar entity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] In most cases, skeletal muscle involvement is associated with other sites of involvement as well. [ 3 ] While 30%–40% of patients with DLBCL will relapse, isolated skeletal muscle relapse is extremely rare,[ 4 ] as was seen in the present case. 18 F-FDG PET-CT is now an integral part of the management of patients with lymphoma, especially DLBCL.…”
mentioning
confidence: 56%